2014
DOI: 10.1002/acr.22191
|View full text |Cite|
|
Sign up to set email alerts
|

Defining Enthesitis in Spondyloarthritis by Ultrasound: Results of a Delphi Process and of a Reliability Reading Exercise

Abstract: Objective. To standardize ultrasound (US) in enthesitis.Methods. An initial Delphi exercise was undertaken to define US-detected enthesitis and its core components. These definitions were subsequently tested on static images taken from spondyloarthritis patients in order to evaluate their reliability. Results. Excellent agreement (>80%) was obtained for including hypoechogenicity, increased thickness of the tendon insertion, calcifications, enthesophytes, erosions, and Doppler activity as core elementary lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
148
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(155 citation statements)
references
References 22 publications
1
148
0
6
Order By: Relevance
“…Generally, the reading reliability was good but with less satisfactory results for acquisition reliability [3,4,23,25,32,34,38,41,44,47,48,51,54,55,61,65,73].…”
Section: Omeract Filter Us Discrimination Capacitymentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, the reading reliability was good but with less satisfactory results for acquisition reliability [3,4,23,25,32,34,38,41,44,47,48,51,54,55,61,65,73].…”
Section: Omeract Filter Us Discrimination Capacitymentioning
confidence: 99%
“…Erosions, enthesophytes, calcification, and cortical irregularities were included as signs of structural damage and therefore suggesting the presence of chronic/inactive US enthesitis. Due to poor agreement, differentiation between acute and chronic enthesitis could not be made [41].…”
Section: Imaging Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of a gold standard for diagnosis, it is unclear whether imaging is a better tool than clinical assessment 27,29,30,31,32,33,34,35 . Outside the clinical trial setting, a combination of clinical suspicion and physical examination plus an objective assessment of inflammation (by ultrasound or MRI) would aid in the proper diagnosis of enthesitis, as well as choice of therapy.…”
Section: Rheumatologymentioning
confidence: 99%
“…Several clinical and US outcome measures for enthesitis in patients with PsA exists; however, their clinical use may be limited by time restraints and lack of training and consensus in the use of these tools 18,21 . The present study showed a significant increase in ICC after training for both LEI and SPARCC scores.…”
Section: Discussionmentioning
confidence: 99%